Recent advances of trichosanthin and its role in diseases. - He, Bin; Yao, Hangping; Zhang, Xiaoqian (Fitoterapia, 2025)
Trichosanthin (TCS), as an alkaline plant-protein classified as a type I ribosome-inactivating protein (RIP), is squeezed out of traditional medicinal plant Trichosanthes kirilowii. Unlike type II RIPs characterized by dual polypeptide chains, TCS exhibits significantly lower cytotoxicity while maintaining potent antiviral activity. These distinctive pharmacological properties have driven growing interest in its therapeutic potential, with accelerating research efforts spanning mechanistic studies, structural optimization, and clinical trials in recent decades. This review will systematically evaluate three critical aspects of TCS research: (1) structure-activity relationships based on crystallographic studies; (2) molecular mechanisms underlying its biological effects; (3) pharmacological properties of TCS and clinical applications of including immunogenicity and delivery optimization. Through critical analysis of recent advances, we aim to identify key knowledge gaps and propose novel strategies for harnessing this plant-derived protein in precision medicine and gain more insight into the mechanism of this natural plant-protein. [Display omitted] • Trichosanthin (TCS) is derived from Trichosanthes kirilowii with lower cytotoxicity and notable pharmacological properties. • TCS exhibits potent antiviral activity, antitumor activity and immunogenicity. • This review aims to identify key knowledge gaps and propose novel strategies for TCS in clinical application.